2008
DOI: 10.1182/blood-2007-05-090654
|View full text |Cite
|
Sign up to set email alerts
|

Accurate identification of paraprotein antigen targets by epitope reconstruction

Abstract: We describe the first successful clinical application of a new discovery technology, epitope-mediated antigen prediction (E-MAP), to the investigation of multiple myeloma. Until now, there has been no reliable, systematic method to identify the cognate antigens of paraproteins. E-MAP is a variation of previous efforts to reconstruct the epitopes of paraproteins, with the significant difference that it provides enough epitope sequence data so as to enable successful protein database searches. We first reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Epitope specificity was also determined by ELISA using recombinant full-length paratarg-7 and recombinant fragments of paratarg-7 as a coat. All 29 paratarg-7 reactive paraproteins were tested by this ELISA and all reacted with recombinant paratarg-7 1-36 and paratarg-7 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] confirming the epitope specificity obtained with the peptide spot assay (Fig. 4).…”
Section: Antibody-binding Epitope Of Paratarg-7mentioning
confidence: 74%
See 1 more Smart Citation
“…Epitope specificity was also determined by ELISA using recombinant full-length paratarg-7 and recombinant fragments of paratarg-7 as a coat. All 29 paratarg-7 reactive paraproteins were tested by this ELISA and all reacted with recombinant paratarg-7 1-36 and paratarg-7 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] confirming the epitope specificity obtained with the peptide spot assay (Fig. 4).…”
Section: Antibody-binding Epitope Of Paratarg-7mentioning
confidence: 74%
“…15 Even though few of these studies convincingly proved that the observed phenomena were indeed caused by binding of the respective paraprotein to its specific antigenic target (e.g., by ''reverse Western'' blotting and/or sequencing of the target antigen as done in this study), these selective observations are often cited to support a causal relationship between the development of an MGUS or MM clone and chronic antigenic stimulation. [1][2][3][4][5][16][17][18][19][20][21][22][23] Similarly, doubts are raised about the paraprotein-mediated reactions with antigens predicted by epitope reconstruction and reported in a recent paper, 24 because the reactions were observed at concentrations of the paraprotein-containing serum of only 1:2,500. In contrast to these reports, our first systematic studies 7,8 did not only convincingly prove the paraprotein-mediated reactivity against the identified antigens, it also revealed a broad spectrum of antigenic targets of paraproteins.…”
Section: Discussionmentioning
confidence: 99%
“…This will hopefully change in the near future as—in addition to expression cloning [145] used in the “paratarg” studies described in Section 3.4—new methods have been developed that lend themselves to identifying and validating specific antigens/haptens recognized by WM-associated mIgM. Epitope-mediated antigen prediction (E-MAP) [148] and high-density peptide microarrays [149] are two promising methods to that end. It is possible that both endogenous (self) antigens and exogenous (microbial) antigens trigger WM.…”
Section: Immunophenotype and Immunological Specificitymentioning
confidence: 99%
“…Epitope-mediated antigen prediction technology may identify antigens reacting with paraprotein antibodies. 30 Identification of these antigens could provide insights into the process by which cells become malignant in WM.…”
Section: Immunoglobulin M Antibodies To Neural Antigensmentioning
confidence: 99%